Differences in alcohol consumption habits between Roma and non-Roma in Northeastern Slovenia - Zelko, Erika (Obzornik zdravstvene nege, 2017)
Introduction: Slovenia has a high level of alcohol consumption. Comparisons of the alcohol consumption habits of the Roma and non-Roma population have yielded conflicting results. The aim of this research was to compare alcohol consumption habits between Roma and non-Roma in a sample population in Northeastern Slovenia. Methods: We conducted a cross-sectional study in which we included 100 representatives of Roma and 100 representatives of non-Roma population, aged 18 to 65 years. The questionnaire used included demographic data (gender, age, marital status, education, and employment) and the AUDIT (Alcohol Use Disorders Identification Test) questionnaire. Two logistic regression models (teetotallers/drinkers and non-hazardous drinkers/other drinkers) were used for the comparison of drinking habits. Results: Roma scored lower on overall AUDIT score (4.51) than non-Roma (4.56). Roma and non-Roma differ significantly regarding teetotallers (39.0 % vs. 16.0 %) and non-hazardous drinkers (38.0 % vs. 64.0 %). Ethnicity was identified to have a statistically significant impact on the studied drinking behaviour: teetotallers (p < 0.001) and non-hazardous drinkers (p = 0.015). Discussion and conclusion: Our aim was to look at the differences between the two groups rather than obtain representative data on the population. Our research also casts a doubt on whether the AUDIT questionnaire is suitable for measuring alcohol abuse.
Keywords: AUDIT questionnaire; drinking habits; ethnicity; etničnost; pivske navade; Roma; Romi; Slovenia; Slovenija; vprašalnik AUDIT